Early Detection of Faults in Induction Motors - Morinigo-Sotelo, Daniel; Romero-Troncoso, Rene; Pons-Llinares, Joan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In modern industries, induction motors are the backbone of numerous applications, powering everything from manufacturing facilities to transportation systems. While they are known for their reliability, unexpected failures can still occur, leading to increased operational costs, facility damage, or service interruptions. "Early Detection and Fault Diagnosis of Induction Motors" is a comprehensive volume that compiles ten innovative journal articles focused on maintaining these machines. The papers explore a variety of techniques that introduce new ideas to the field.